2018
DOI: 10.1097/hp.0000000000000865
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Fluoroscopic Peak Skin Dose Using Manual Calculations

Abstract: Not all healthcare providers can afford to purchase commercially available programs that can quickly and easily provide peak skin dose estimations for patients undergoing diagnostic and international fluoroscopic procedures. The air kerma reference point exposure, Ka,r, available on all equipment manufactured after 2006, may over or under estimate the patient's peak skin dose. The total air kerma reference point exposure provided at the end of a case might be on the order of 20 Gy for a patient, indicating tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…From measurements on a table with a 5-cm thick mattress, Bordier et al [6] observed about 10% difference in the beam intensity comparing Postero-Anterior (PA) and Right Anterior Oblique (RAO) 40 • projections. In agreement with this, DeLorenzo et al [4] observed a decrease of 6% for RAO 40 • projection. It should be noted that, in addition to the mattress attenuation, Dose Map accounts explicitly for the contribution of the scatter originating from the mattress.…”
Section: Comparison Of Softwaresupporting
confidence: 65%
See 1 more Smart Citation
“…From measurements on a table with a 5-cm thick mattress, Bordier et al [6] observed about 10% difference in the beam intensity comparing Postero-Anterior (PA) and Right Anterior Oblique (RAO) 40 • projections. In agreement with this, DeLorenzo et al [4] observed a decrease of 6% for RAO 40 • projection. It should be noted that, in addition to the mattress attenuation, Dose Map accounts explicitly for the contribution of the scatter originating from the mattress.…”
Section: Comparison Of Softwaresupporting
confidence: 65%
“…Since significant dose differences can occur depending on whether a given parameter is accurately considered in the MSD calculation, available SDC software solutions were collected and analysed according to their calculation algorithms and their specific features [4,5].…”
Section: Methodsmentioning
confidence: 99%